KEUNTUNGAN MEDIASI DALAM PERKARA PERCERAIAN DENGAN ADANYA PERMA NOMOR 1 TAHUN 2016 - Rahma, Nurlaili (Ahkam: Jurnal Hukum Islam, 2018)
ABSTRACTSupreme Court Regulation No. 1 Year 2016 gives a big change to every seeker of justice and everyone who is involved in it because this new rules revise many regulation compared to the previous one, in order to make mediation more efective and efficient. The success of mediation is not only determined by regulation, but also the goodwill of both parties having a legal dispute, the support of judge, the support of lawyer, and mediator’s profesionalism to conduct mediation. Therefore, the capability non judge mediator must be upgraded to decrease the rate of divorce in the court because every year the number of case always increases due to various problem.Keywords: Mediasi, Perceraian, PERMA No. 1 Tahun 2016